Beyond a common joy: an introduction to Shakespearean comedy - Olson, Paul A. (University of Nebraska Press, 2008)
On historical understandings of Shakespeare's works -- Shakespeare and the invention of grand comic form -- Shakespearean comedic myths -- Biblical story and festival enter Shakespearean comedy -- Empire and conquest in the comedies -- Measure for measure as form, myth, and scripture